Composition and temporal variation in the diet of beluga whales, derived from stable isotopes - Marcoux, Marianne; McMeans, Bailey C.; Fisk, Aaron T.; Ferguson, Steven H. (Marine Ecology Progress Series, 2012)
The diet of individuals within a species commonly differs among sex and age classes because of differences in energy requirements and physiological needs. Belugas Delphinapterus leucas show a high level of sexual habitat segregation and dimorphism that could result in differences in diet between the sexes. Here, we used stable isotopes of carbon ( 13C) and nitrogen ( 15N) from muscle and skin samples of 88 belugas, and likely prey species, to investigate how beluga diet in Cumberland Sound (Nunavut, Canada) varied between sexes, among age classes, and over time from 1982 to 2009. Based on linear mixed-effects models, older belugas had higher 13C and 15N than younger individuals of both sexes, suggesting that older individuals feed on more benthic, higher trophic-position prey than younger individuals. We also found a strong, decreasing trend in both 13C and 15N values over time, indicating either a temporal shift in beluga diet or an ecosystem-wide change in isotope values. Based on stable isotope mixing models performed on belugas sampled since 2000, both males and females fed primarily on Arctic cod Boreogadus saida and capelin Mallotus villosus. The latter is a recent invader to this ecosystem, which could explain the temporal shift in stable isotopes of the Cumberland Sound belugas. © Inter-Research 2012.